Antenatal thyroid screening and its clinical correlation - Sisodia, Juhi; Samant, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The study of hypothyroidism in pregnancy was done with the aim of determining the effect of hypothyroidism on maternal and perinatal outcome. This study also aimed to decide whether universal screening of pregnant women for hypothyroidism is justified. Methods: A prospective observational study was done over a period of 1 year from October 2011 to September 2012, on pregnant women attending the OPD of Obs and Gynae department. Serum TSH is the most convenient and best test to diagnose hypothyroidism in pregnancy in first trimester. Ideal serum TSH level during pregnancy is 0.5-2.5µIU/ml in first trimester and 0.5-3µIU/ml in second and third trimester. First trimester booking visit is the ideal time for initial evaluation. Thereafter serum TSH should be measured at 6 weeks interval for necessary dose adjustments. Levothyroxine is the drug of choice. It should be started at 1.6-2µg/kg/day. If serum TSH is raised but fT4 is normal, treatment can be started with 25-75µg/day. Results: Inadequately treated hypothyroid pregnant women had higher incidence of maternal complications in comparison to adequately treated hypothyroid patients, like threatened abortion (11.1% vs 1.5%), antepartum hemorrhage (7.4% vs 1.5%), premature rupture of membrane (14.8% vs 3.0%), preterm labour (18.5% vs 1.5%), postpartum hemorrhage (9.3% vs 4.5%), anemia (16.7% vs 9.1%) and intrauterine death (9.3% vs 0%). Perinatal complications were also higher like fetal distress (33.3% vs 13.6%) and low birth weight (16.7% vs 4.5%). Incidence of caesarean section was higher in hypothyroid women in comparison to control group (29.2% vs 19.2%). Conclusions: This study shows that there is an association between inadequately treated hypothyroidism and adverse maternal and perinatal outcome. Those who were detected early and adequately treated had outcome similar to control group.